AB1175 Decreased autophagic activity in t lymphocytes from patients with newly diagnosed systemic lupus erythematosus. (15th June 2017) - Luo, X; Liu, Y; Yang, M
Abstract : Background: Alterations in T-lymphocyte homeostasis have been suggested to play a key role in the pathogenesis of SLE. Autophagy is now emerging as a core player in the development and the functioning of the immune system. Objectives: we investigated the autophagic behavior of T cells from patients with SLE. Methods: Thirty patients with SLE and twenty-five healthy subjects matched for gender and age were recruited. The levels of mRNA encoding ATG5, ATG7, Beclin-1 and LC3 was determined by quantitative real-time polymerase chain reaction (qPCR), and evaluate autophagy activity in T cells by flow cytometry. The number of autophagic structures was examined by TEM in T cells from SLE patients and healthy controls. Results: We documented a decreased of mRNA expression of LC3 and Atg7 in T cells from patients with SLE (t=2.282, P=0.027; t=3.573, P=0.001).A decreased percentage of autophagic cells was comfirmed in T cells from patients with SLE, as compared to healthy donors by flow cytometry (t=2.034, P=0.047).no significant correlations between autophagy levels in T cells and the disease activity of patients were observed (p>0.05). Conclusions: Our results indicate that autophagy activity in T cells from SLE patients is decreased, which may contribute to the development of SLE, and thus that resetting autophagic activity may be an important therapeutic goal in this autoimmune disease. Acknowledgements: The authors thank Dr Liu Qinsong, and Mr Xia Yanhui for their technical assistance. Disclosure of Interest: None declared